Innovative Educational Broadcasting: UGTV's Influence on Gunadarma Students and the Wider Community - Edy Prihantoro; Noviawan Rasyid Ohorella; Muhammad Adnan Pitchan; Nikolas Ferdinand (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung Sunan Gunung Djati Bandung, 2024)
Television remains a medium for delivering information and entertainment, to communities, particularly in areas with unequal access to the internet, so television becomes their primary source. This study aimed to explore how UGTV is utilized to deliver educational content to students of Gunadarma University and the wider community. Using a qualitative method with a constructivist paradigm, this study was grounded in the Media Ecology Theory. Data were collected through observation, in-depth interviews, documentation, and literature studies. The findings revealed that UGTV, as an educational digital television platform, effectively provides academic and innovative content useful for the community, particularly students. The contents are produced and packaged to be informative and appealing to the community.